Provisioning policies for non-performing loans: How to best ensure a "clean balance sheet"? - Mark Wahrenburg (Goethe University Frankfurt, SAFE - Sustainable Architecture for Finance in Europe, 2017)
New provisioning rules introduced by IFRS 9 are expected to reduce the procyclicality of provisioning. Heterogeneity among banks in the procyclicality of provisioning may not only reflect the formal accounting rules, but also variation in discretionary provisioning policies. This paper presents empirical evidence on the heterogeneity of provisioning procyclicality among significant banks that are directly supervised by the ECB. In particular, this paper finds that provisioning is relatively procyclical at banks that have i) high loans-to-assets ratios, ii) high shares of non-interest income in total operating income, iii) low capitalization rates, and iv) low total assets. Supervisory guidance provided to banks on how to implement IFRS 9 has mostly been of a qualitative nature, and may prove inadequate to prevent an undesirably wide future variation in provisioning among EU banks.
urn:nbn:de:hebis:30:3-452020; Additional information: This paper was provided at the request of the Committee on Economic and Monetary Affairs of the European Parliament and commissioned and drafted under the responsibility of the Economic Governance Support Unit (EGOV) of the European Parliament.
Keywords: 330; IFRS 9; provisioning rules; EU banks